Penerapan Model Discovery Learning dalam Pembelajaran IPS Terpadu Pada Siswa Kelas VII SMP Negeri 3 Colomadu Tahun Ajaran 2014/2015 - Astuti, Puji, Dra. Titik Asmawati, SE., M.Si (2015)
The purpose of this study was to describe: 1) measures the application of discovery learning model of Integrated Social learning in class VII SMP Negeri 3 Colomadu academic year 2014/2015; 2) the advantages and disadvantages of the application of discovery learning model of Integrated Social learning in class VII SMP Negeri 3 Colomadu academic year 2014/2015. This study is a qualitative research. Data collection technique used is the technique of interview, observation, and documentation. Analysis of the data used is an interactive model that consists of a collection of data (data collection), data reduction (data reduction), presentation of data (data display), and conclusion (conclusion drawing). The validity of test data using the credibility of the data with triangulation consisting of triangulation of sources and techniques. The results showed that 1) the application of discovery learning in Integrated Social learning in SMP Negeri 3 Colomadu characterized by active students in the classroom, and the students directly involved in teaching and learning activities. Steps discovery learning first phase Indonesian teacher publishes maps and drawings of economic activity, the second stage students identify issues in accordance with the sub-theme of economic activity and utilization of natural resources, the third phase students read textbooks Integrated IPS to seek information or troubleshooting, The fourth stage students write the results of the discussion, then students present and at the end of the students' learning with the teacher make conclusions; and 2) the excess application of discovery learning that students are very enthusiastic in learning, can improve the ability of students to solve problems, and the knowledge gained individual student. Disadvantages discovery learning takes a long time, does not apply in all themes / topics of learning, because the material is very wide Integrated IPS.